Dry matter losses and fermentative profile of sorghum silages cultivated in the Western Amazon (Research, Society and Development, 2022)
The use of silage in feed for ruminants and especially in cattle breeding has been widely used, so that this can contribute to raising the productive potential of the animal, and consequently, increasing the profitability of production systems. sorghum is a forage plant that can be compared to corn in relation to its agronomic value and nutritional value. Thus, sorghum appears as an interesting alternative, since it is more resistant to drought, given its ability to recover and produce grains and more forage after a period of drought. The objective of this study was to evaluate the dry matter (DM), dry matter losses during fermentation and also the fermentative quality of the silages of five sorghum cultivars in the Western Amazon. A completely randomized experimental design was used, with five treatments and four replications, consisting of the following cultivars: SAC - Siles Sacarino Ceres; BIC - Siles Biomass Ceres; SIC - Siles Silageiro Ceres; SIV- Silageiro Silageiro Volumax and SIE - Silageiro Silageiro Embrapa. The cultivars were ensiled in experimental PVC tube silos. After 50 days of storage, the silos were opened, discarding an upper portion of 5 cm of each silo and then the MS analyzes, dry matter recovery (RMS), effluent losses (PE) and losses by gases and analysis of the fermentative profile: pH, acetic acid (AC), propionic acid (AP), butyric acid (AB) and lactic acid (LA). The contents of DM, pH, RMS, PE and PG differed (p